HUBUNGAN KUALITAS TIDUR TERHADAP KONSENTRASI BELAJAR SISWA KELAS VII-3 DI SMPN 4 MEDAN - Sitorus, Grace Elicia; Samosir, Martha Indah; Sagala, Prihatin Ningsih; Sibarani, Khoirunnisa; Dhuha, Nadira Kaylana; Munthe, Tiolina Maria (Mandalika Mathematics and Educations Journal, 2025)
Learning concentration plays a crucial role in students' academic success and can be influenced by various factors, including sleep quality. This study examines the relationship between sleep quality and mathematics learning concentration among seventh-grade students (VII-3) at SMPN 4 Medan. A descriptive correlational method with a quantitative approach was used. Data were collected using a sleep quality questionnaire based on the Pittsburgh Sleep Quality Index (PSQI) and a learning concentration questionnaire. Statistical analysis included the Chi-Square test, Pearson and Spearman correlation, and Odds Ratio estimation. Results showed that 54.5% of students had poor sleep quality, while 45.5% had good sleep quality. Regarding concentration, 54.5% of students exhibited good concentration, while 45.5% struggled to focus. Statistical tests confirmed a significant relationship between sleep quality and learning concentration (p = 0.007), with a moderate positive correlation (r = 0.467). The Odds Ratio indicated that students with good sleep quality were eight times more likely to have high concentration. These findings emphasize the importance of proper sleep habits in improving students' focus and academic performance.